The baptism of Probus (Acts of Xanthippe, Polyxena, and Rebecca, XXI): a translation and commentary - Pavão, Fernando (2023)
The narrative of the baptism of Probus marks the end of the first part of the plot of the Acts of Xanthippe, Polyxena, and Rebecca, a Christian novel written in Late Antiquity. This is an important passage for establishing the date of composition, with a possible intertextual relationship and a non-dictionary term, which may indicate an error in the passage from uncial to minuscule manuscripts. The purpose of this article is to present the translation of this passage (Acts of Xanthippe, Polyxena, and Rebecca, XXI) and a discussion of the relevant items for establishing the date of the composition, as well as briefly introducing the work to contextualize the study.